Optimization of Kefir Grains Production and Evaluation of Antagonistic Activity against Pathogenic Bacteria - Suhad Redha Al- Tayie (Journal of Global Pharma Technology, 2018)
The bioactive properties and therapeutic importance for kefir grains encourage us to study the optimum culture conditions for maximum propagation and production. The kefir grains were cultured at different change conditions included (type of culture media, temperature, incubation time, and agitation speed). Additionally, the antagonistic activity for kefir was evaluated  against four pathogenic bacteria (Staphylococcus aureus , Staphylococcus saprophyticus, Esherichia coli O157 and  Klebsila penumonia) in two different methods ;First, the antibacterial activity was estimated by using kefir grains and  measuring the inhibition zone of growth .Second , the antibacterial activity was estimated by using the kefir whey  (fermented milk supernatant )after clarification process . The results showed The optimum culture condition  were achieved  by using the skim milk as culture media , incubation at 37 ◦C , for 24 h at static condition , these conditions lead to increase the growth rate to about  55.6% (70.1 gm/L), while the using of culture media supplemented with 5% glucose ,1% lactose and 5% yeast extract , the growth rates were (45.8 %, 41.3 % and 2. 2 %) respectively ,with biomass about (65.6 , 63.4 and 46 gm/L) respectively , in general ,these supplement lead to reduce the  rate of kefir grain biomass. The result of antibacterial activity of kefir grain revealed the highest inhibition zone was 4.05 cm for S.aureus, 3.55 cm for both S. saprophyticus and K. penumonia while the least inhibition zone was 2.9 cm for E. coli O157 strain, whereas the antagonistic activity of kefir whey     showed the inhibition rates were 86.6 %  for S. aureus, 90.7% for both S. saprophyticus and K. penumonia and 89.6 % for E. coli O157 strain . We concluded from this study the optimization of growth environment is very important for achieving the maximum production of kefir grains biomass and the kefir grain evaluated had high antagonistic activity toward the pathogens .This indicate potential using these grains as functional food.Keywords: Kefir grain; Culture conditions; Biomass; Antagonism; whey; Pathogenic bacteria.